Strategic Marketing Public Relations for Brand Elevation: A Case Study of the #JacquelleDisneyEdition Campaign - Qausya, Anindya Aulia; Bernadette, Sophia (LSPR Institute of Communication & Business, 2023)
The strategic Marketing Public Relations (MPR) efforts of Jacquelle Beaute, especially through their collaboration with Disney, have significantly enhanced brand awareness. Using the three fundamental Public Relations functions defined by Edward L. Bernays, the brand has effectively communicated product knowledge via digital platforms like Instagram and TikTok, organized engaging events to influence public behavior, and maintained strong public relationships. Key strategies involving publication, events, sponsorship, and media identity have played vital roles. Publications on Instagram and TikTok, supported by beauty influencer reviews, have spread product knowledge, despite challenges in influencer selection. Events, including the grand launch of the Disney Ariel collaboration, have boosted brand awareness by reflecting Jacquelle Beaute’s unique characteristics. Sponsorships, particularly targeting young adults in universities, have expanded their reach through word-of-mouth promotion. The distinctive media identity, characterized by sustainable and multitasking products and unique Disney-themed packaging, has made their products easily recognizable. While the research indicates that only four out of the seven MPR tools outlined by Kotler and Keller (2012) were effectively utilized, Jacquelle Beaute's efforts have generally been successful, achieving Brand Recall and Brand Recognition levels of awareness. However, there is room for improvement in influencer selection and pricing strategies to broaden their audience. Overall, Jacquelle Beaute's strategic use of MPR tools, particularly through digital media and well-executed events, underscores the importance of a cohesive approach in building brand awareness.